URGENSI PENDIDIKAN POLITIK BAGI PEREMPUAN - Soeharto, Achmad (MUWAZAH, 2011)
Abstract: Through political education of women are expected to know and understand the rights and obligations as citizens, so that women have a significant role in developing democracy and intelligent in determining political attitudes. It is time women are placed as the subject in the political arena, not solely as a political object, which appears to be merely exploit them for elite interests or political party. Conditions, due to a lack of political education for women. For that a good political education, are expected to materialize the political role of women in the life of society, nation and the state towards the realization of a democratic civil society and justice. Thus the urge strengthening women's political rights should be increased primarily through the regulation / legislation in favor of women. Empowerment of women in various aspects of social life and civic culture, very urgent to increase women's political role.